The waiting room of uncertainty: digital patient support for potentially bad news—a scoping review - Kellermann, Martina; Wetterauer, Charlotte; Kullak-Ublick, Gerd A.; Cheetham, Marcus (Frontiers in Digital Health, 2025)
Breaking bad news (BBN) of serious or life-threatening diagnoses is common in oncology and often induces significant patient anxiety and distress. The anticipation of such news can also cause considerable distress, prompting patients to adopt proactive coping strategies, such as information seeking, while waiting for the news. Although the use of traditional and emerging digital technologies to assist patients across diverse aspects of cancer care has grown considerably, their role in assisting patients while they await the possibility of receiving bad news (RBN) remains unclear. We conducted a scoping review, following PRISMA-ScR guidelines, to identify studies on digital interventions, at any stage of realization, that aim to aid patient preparation for potential bad news, to map characteristics of these interventions (e.g., target diagnoses, design features) and to assess reported outcomes from usability to implementation. Using broad search terms related to digital technology, patient support and RBN and/or BBN in oncology across many databases, we identified 1020 articles. Most of these targeted healthcare professionals and BBN training (delivered with digital technology) and some referenced digital technology in the context of patients and bad news. However, none of the 22 articles that reached full text screening addressed any form of digital support for patients in relation to RBN. These findings highlight a striking gap in the use of digital support for this personally significant aspect of the patient journey. We contextualize this gap by discussing the value of digital support for RBN from a patient perspective, addressing why the news waiting period has received no attention in the BBN literature and highlighting the conceptual and practical intersections between RBN and shared decision-making (SDM), including consideration of common and distinct design features of patients aids for RBN and for SDM. Finally, we outline future research directions to address this significant and unmet need.